1999
DOI: 10.1136/adc.80.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Growth of long term survivors of liver transplantation

Abstract: Objective-To assess growth in survivors of liver transplantation. Study design-Growth was studied in 105 children up to seven years after liver transplantation. Results-At transplantation, mean height standard deviation score (zH) was −1.22 but 19% of patients were severely growth retarded (height below 0.4th centile). Growth and pubertal retardation were seen in the first six months after liver transplantation. Significant catch up in growth and puberty continued for more than five years. At five years, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 16 publications
9
73
2
Order By: Relevance
“…In the BAS group, no death was considered to be definitely related to BAS. In one case we considered the cause of death to be possibly related to study medication: a 17-year-old boy transplanted for acute liver failure secondary to liver trauma with a whole liver from a 79-year-old donor died on the 9th postoperative day because of enterococcus sepsis and multiple or- 2 Seven deaths in 12-month study period analyzed, steroids, n = 3; basiliximab, n = 4.…”
Section: Patient and Graft Survival Technical Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the BAS group, no death was considered to be definitely related to BAS. In one case we considered the cause of death to be possibly related to study medication: a 17-year-old boy transplanted for acute liver failure secondary to liver trauma with a whole liver from a 79-year-old donor died on the 9th postoperative day because of enterococcus sepsis and multiple or- 2 Seven deaths in 12-month study period analyzed, steroids, n = 3; basiliximab, n = 4.…”
Section: Patient and Graft Survival Technical Complicationsmentioning
confidence: 99%
“…However, steroid avoidance could be beneficial, particularly in pediatric recipients because, when administered for a prolonged period, they are associated with multiple severe side effects including infections, arterial hypertension, glucose intolerance, hyperlipidemia, osteoporosis and growth impairment (2)(3)(4). Moreover, work in rodents suggests that the administration of steroids may interfere with the development of immunological tolerance, as well as with the process of hepatic regeneration (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients taking steroids carry an increased risk for developing malignancies, especially lymphomas and skin cancers [104] . Detrimental metabolic effects of steroids are wide ranging and are of particular concern for the pediatric transplant patient [105][106][107] . In terms of hospital costs, the calculated 10-year cumulative expense for steroid-related complications in adult kidney recipients has been shown to be 5300 $ per patient per year [108] .…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Pre-transplant factors including height Z-score at transplant, age at transplant, gender, and underlying diagnosis have all been reported to be important in determining height growth 26,[49][50][51] . Other variables including donor age, post-transplant hepatic vein stenosis, and steroid dose have also been reported to be important determinants of growth in children [52][53][54] . There remains however, limited data on long-term growth after liver transplantation in childhood.…”
Section: Am Very Grateful To Ms Kerrie Beale and Mr Charlton Noblementioning
confidence: 99%
“…There remains however, limited data on long-term growth after liver transplantation in childhood. Several studies have reported children to attain height around the 25-30 th centile, 7-10 years after transplant 34,35,54 . This duration of review however does not allow for full growth potential as many children will not complete growth until aged 20 years.…”
Section: Am Very Grateful To Ms Kerrie Beale and Mr Charlton Noblementioning
confidence: 99%